IMPLEMENTASI PERATURAN OJK NO 11 /POJK.03/2020 TERHADAP PENANGGUHAN DAN KERINGANAN HUTANG PIUTANG DEBITUR LEASING DALAM PANDEMIK COVID 19 - Junnytte Juliana Pinca; Linda setiawati; Kuntri Selvilia Lidya Sari; Nabella Lestyanti Geraldin; Lorensya Mulyagita Anggraeni (Fakultas Hukum Universitas Narotama, 2022)
The Government of the Republic of Indonesia through the Otoritas Jasa Keuangan (OJK) issued a regulation concerning the National Economic Stimulus as a Countercyclical Policy on the Impact of the Corruption Virus Disease 2019 with Number 11 / POJK.03 / 2020. Countercyclical which means increasing a capital, implemented in two policies; deciding the quality of assets and restructuring credit and finance. Restructuring credit and finance applicated to several forms such as deferment of payment, rescheduling, reduction of interest rates, reduction of fines, and extension of loan term. Each bank or take different forms but remain in the corridor of translating Countercyclical policies. Likewise, the form of relief provided to debtors is adjusted to the circumstances and prospects of the debtor. With this regulation, it is easy for business people and some MSME sectors to continue to survive in the midst of a covid-19 virus pandemic. The procedure for implementing the Otoritas jasa Keuangan rules is indeed adjusted by each Bank and multi-finance company, but the debtor or business actor can apply for a credit suspension in accordance with applicable regulations. Keywords: Covid-19 Pandemic, Implementation of OJK Regulatian, Deferment and Relief, Debts and Receivables Leasing Debtor